The Use of Media and Demonstration Methods to Increase Understanding of Building Space in Third Grade Students Min 3 East Jakarta - Tuti Rohayati (Journal of Social Research, 2023)
In the curriculum of the education unit, there are five subject families, namely religion and noble morals, citizenship and personality, science and technology, aesthetics, physical, sports, and health. To improve student achievement in mathematics lessons, especially increasing understanding of building space through the use of media and demonstration methods for third grade students (3) MIN 3 Cijantung Kopassus complex East Jakarta. This research uses two cycles, each cycle consists of three meetings, namely the implementation of class action research cycle I will be carried out on February 7, 8, and 24, 2023 while the second cycle will be carried out on February 21, 28, 2023. This type of research is classroom action research which is research that aims to improve the effectiveness and efficiency of the teaching and learning process. Research is carried out in the classroom. Research activities in cycle I, at the first meeting researchers began the activity by filling in student attendance, praying, preparing teaching materials, models, props, reminding how to sit well when writing and reading, singing together while clapping, and repeating and reminding past lessons. With media and demonstration methods, it can increase the understanding of building space in grade 3 MIN 3 Cijantung MIN 3 Cijantung students, with evidence of an increase in learning outcomes described as follows: the first cycle of 29 students, which is categorized either as many as 9 people or 27%, sufficient categories as many as 17 people or 58.6% and categories less than 4 people or 1.16%.